2002
DOI: 10.4049/jimmunol.169.4.1922
|View full text |Cite
|
Sign up to set email alerts
|

Repression of AP-1 Function: A Mechanism for the Regulation of Blimp-1 Expression and B Lymphocyte Differentiation by the B Cell Lymphoma-6 Protooncogene

Abstract: The B cell lymphoma-6 (BCL-6) transcriptional repressor protein is an important regulator of B cell differentiation and is strongly implicated in the development of B cell lymphoma. Expression of the Blimp-1 transcription factor, which is critical for promoting B cell differentiation into plasma cells, is repressed by BCL-6. We have investigated the mechanism for how BCL-6 represses Blimp-1 transcription, and have found that BCL-6 regulates the Blimp-1 promoter through a novel mechanism involving AP-1 elements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
158
1

Year Published

2008
2008
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 177 publications
(168 citation statements)
references
References 29 publications
9
158
1
Order By: Relevance
“…2). Possible candidate cis-elements located in this larger construct could be the binding sites for AP1 TF, which has been reported to increase the promoter activity in the absence of Bcl-6 [15]. In addition, a binding site (Maf response element site) for the repressor factor Bach2 that binds to the same site as the AP1 factor has recently been described [21].…”
Section: Identification Of Dna Sequences Required For Prdm1 Transcripmentioning
confidence: 91%
See 1 more Smart Citation
“…2). Possible candidate cis-elements located in this larger construct could be the binding sites for AP1 TF, which has been reported to increase the promoter activity in the absence of Bcl-6 [15]. In addition, a binding site (Maf response element site) for the repressor factor Bach2 that binds to the same site as the AP1 factor has recently been described [21].…”
Section: Identification Of Dna Sequences Required For Prdm1 Transcripmentioning
confidence: 91%
“…On the basis of the PRDM1 transcript levels changes [13] it has been proposed that Bcl-6 represses PRDM1 expression at the germinal center B cell stage. Regulation studies on the human PRDM1 gene promoter have shown that Bcl-6 and Bach2 have recently been proposed as a repressor for human PRDM1 gene transcription [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…A similar mechanism seems to function also in T cells [10]. Although direct binding of Bcl6 to PRDM1 has been characterized, it may not be a prominent mechanism, since inhibition of AP-1 function has been proposed as a mechanism for Bcl6-mediated PRDM1 repression [26]. Also, IRF4 has been suggested as a Bcl6 target that could contribute to PRDM1 expression [27].…”
mentioning
confidence: 99%
“…Bach2 has been shown to repress PRDM1 expression through two different MAREelements, one within the promoter [40] and the other next to the Bcl6 response element 1 (BRE1) within the fifth intron of the PRDM1 gene [41]. Thus, Bcl6 appears to use yet another mechanism to ensure the repressed state of PRDM1 in B cells in addition to the previously described competition for DNA binding with STAT3 [51], inhibition of AP-1 function [26] and direct binding to BRE1 in the PRDM1 gene [23]. Importantly, the mechanism that involves Bach2 would employ activation of transcription by Bcl6 as suggested for regulation of Cxcr5, Il6r and Il21r in the context of follicular T helper-cell development [11].…”
mentioning
confidence: 99%
“…GC are dynamic and specialized structures in the secondary lymphoid organs within which B cells undergo immunoglobulin class switch recombination and somatic hypermutation to produce diverse, high-affinity antibodies (17,26). Widely considered to be the master regulator of the GC stage of B-cell development, BCL6 maintains the GC-specific gene expression program by silencing genes involved in B-cell activation (CD69, CD80, and NF-B1), response to DNA damage (TP53 and ATR), cell-cycle regulation (CCND2, CDKN1B, and CDKN1A), and plasma cell differentiation (PRDM1) (25,29,34,37,38,40,41). Thus, neither the memory nor the plasma cell differentiation program can be initiated until expression and activity of BCL6 are extinguished by GC exit signals.…”
mentioning
confidence: 99%